ANALISIS KEBERBAKATAN OLAHRAGA DITINJAU DARI LATAR BELAKANG GENETIKA DAN DUKUNGAN SOSIAL - Sya'rani, Ahmad Zaeri; Sutresna, Nina; Sidik, Dikdik Zafar (UNIVERSITAS NEGERI MAKASSAR, 2020)
This study aims to determine the effect of genetic background on giftedness in sports. The research method used is the study of literature. Data obtained through Google Schooler search; Science Direct; Taylor and Francis; Scopus; PsycInfo; Proquest; and Pubmed by entering keywords; 'Talent', 'sports talent', 'genetic', 'social support', 'network', 'parent', 'coach', 'peer', 'talent identification' and 'talent development'. Next analyze the search resultsto get answers about the influence of genetic background on the giftedness of sport. Descriptive analysis techniques are used to explain the processed quantitative data. The results showed that genetic background and social support influence sports talent